Computation of damping derivative of an Ogive at highspeed flow - Ayesha, Shabana; Crasta, Asha; Ridwan, R; Khan, Sher Afghan (The Scientific Press, 2022)
This paper aims to derive an expression for the damping derivative of an ogive in pitch. The Ogive shape is achieved by superposing an arch on the cone. The inertia levels considered are M = 5, 7, 9, 10, and 15. The contemporary theory applies to the connected shock case & the Mach M2 behind the shock M2 ≥ 2.5. Damping derivatives are examined for ogive for γ = 1.4 at various semi angles for differing pivot positions and Mach numbers and λ = ± 5, 10. Results indicate a continued decrease in stability derivatives. However, the damping derivatives turn independent of Mach M for Mach more than ten— with a surge in the cone angle, a continued rise in the damping derivatives attained.